Modelo de negocio para crear una empresa constructora exitosa (2021)
In the creation of a company there are several steps that must be taken into account to achieve business success, one of them that has a direct impact is the business model to use, through this work one will be developed for an established construction company, this model will be made with the canvas tool created by Alex Osterwalder and Yves Pigneur. The business model produced will be the initial approach to bringing the company to good market positioning, growing business, acquiring and maintaining more customers and earning good revenue.